ESTIMATION OF YIELD LOSSES IN COTTON DUE TO MAJOR FUNGAL FOLIAR DISEASES - SK ROSHAN BABA*, S.L. BHATTIPROLU, V. PRASANNA KUMARI; CH. CHIRANJEEVI (The Journal of Research ANGRAU, 2022)
The experiment was conducted at Regional Agricultural Research Station, Lam, Guntur during kharif 2019-20 to estimate the losses due to major fungal foliar diseases including Alternaria leaf spot, Corynespora leaf spot and grey mildew in two BG II hybrids and one straight variety of cotton. Two sprays of propiconazole @ 0.1% were applied at 60 DAS and 75 DAS; third spray with metiram + pyraclostrobin @ 0.1% at 90 DAS and final spray of carbendazim @ 0.1% were applied at 105 DAS. Disease observations were recorded to assess the severity of fungal foliar diseases of cotton in protected and unprotected plots. Percent increase in unprotected plots varied from 64.65 to 84.95, 85.77 to 87.12 and 70.59 to 78.40 when compared to plots protected for Alternaria leaf spot, Corynespora leaf spot and grey mildew, respectively. Yield data in protected and unprotected plots revealed that percent seed cotton yield loss of 16.14 in Jaadoo BG II, 20.34 in RCH 2 BG II and 26.28 in L 1060. The highest ICBR was obtained for Jaadoo BG II (26.61) when compared to RCH 2 BG II (19.95) and L 1060 (19.46).